Commentary: "Up" within "Down" - Hatten, Robert S. (Empirical Musicology Review, 2015)
This commentary considers ways in which meter implies a virtual environmental field, one that has close correlations with dancers’ actual experiences of movement within gravitational constraints, despite their verbal descriptions that might suggest the contrary. Upward movements on downbeats are interpretable as virtual agents’ expenditures of energy against virtual gravitational constraints, akin to those dancers experience in ballet. Thus, “up” as movement can imply “down” as gravitational field.